2018
DOI: 10.1590/1980-5373-mr-2017-0508
|View full text |Cite
|
Sign up to set email alerts
|

Cell and Bacteria-Baterial Interactions on the Ti10Mo8Nb Alloy After Surface Modification

Abstract: The purpose of this study is the surface modification of Ti10Mo8Nb experimental alloy by using TiO 2 nanostructure growth. Ingots of the Ti10Mo8Nb experimental alloy were produced by fusion from sheets of molybdenum, niobium, and titanium commercially pure in an arc melting furnace under argon atmosphere. The potentiostatic anodic oxidation was performed using an electrolyte formed of glycerol and H 2 O (1: 1 by vol.) with the addition of 2.7% (w/v) NH 4 F under 20 V for 3 h at room temperature. After the surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…These results have led to an increased interest in studies in this area. Some promising alloys developed recently include: Ti-Mo-Nb [4,7,8], Ti-Mo-Nb-Zr [3,9], Ti-Nb-Cu [10], Ti-Zr-Nb [11], Ti-Nb-Sn [12], Ti-Nb-Ta [13,14], Ti-Nb-Zr-Mn-Sn [15], Ti-Mo-Nb-O [16], Ti-Nb-Zr-Ta [16], Ti-Nb-Zr-Ta-Sn [1], and Ti-Ta-Nb-Sn [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…These results have led to an increased interest in studies in this area. Some promising alloys developed recently include: Ti-Mo-Nb [4,7,8], Ti-Mo-Nb-Zr [3,9], Ti-Nb-Cu [10], Ti-Zr-Nb [11], Ti-Nb-Sn [12], Ti-Nb-Ta [13,14], Ti-Nb-Zr-Mn-Sn [15], Ti-Mo-Nb-O [16], Ti-Nb-Zr-Ta [16], Ti-Nb-Zr-Ta-Sn [1], and Ti-Ta-Nb-Sn [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Ti-Mo-Nb alloys have been evaluated as an option for biomedical applications [ 27 , 28 , 29 , 30 , 31 , 32 ]. The study of Ti 10 Mo 3 Nb, Ti 10 Mo 7 Nb, and Ti 10 Mo 10 Nb alloys indicated a microstructure with equiaxial grains, a beta-phase in the alpha-matrix, and an increase in the content of the beta-phase with the increase in the concentration of niobium in the composition.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies showed strong adhesion, good proliferation, and cell differentiation results like those for CP Ti. The Ti-Mo-Nb system also showed no cytotoxicity or inflammatory response [ 30 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation